The impacts of red-emitting phosphor Mg8Ge2O11F2:Mn4+ on the color rendering index of convex-dual-layer remote phosphor WLEDs at 5600 K - My Hanh Nguyen Thi; Phung Ton That; Nguyen Doan Quoc Anh (Universitas Ahmad Dahlan, 2021)
The poor color rendering index (CRI) induced by mono chip and phosphor configuration in the conventional white-light light-emitting diode (LED) urges for developments in both packaging and material, thus, a modern lighting solution was introduced. The dual-layer phosphor package is an innovative configuration that can retain the lumen output of conventional white light emitting diode (WLED) while also enhancing color quality. The structure of dual-layer phosphor package that was proposed includes two chips and one phosphor. The priority in this research is to keep improving the lighting properties of WLED, therefore, further experiments with this dual-chips and dual-phosphor package are conducted. The lighting properties of LED are measured multiple times with its nitride-based phosphor being altered in proportions and densities each occasion, the results are calculated with a color design model made specifically to monitor and adjust the color of white-light from LED to match desired outcome. The WLED at 5600 K correlated color temperature (CCT) is the sole research object of the experiments. The measured parameters from the 5600 K WLED and the color coordinates of CIE 1931 simulated from the color design model show that 0.0063 is the highest possible discrepancy at 5600 K (CCT). The information from this manuscript provide the manufacturers with the most efficient approach to create a white LED that has good color quality, high CRI and luminous flux.